Enhanced photocatalytic activity of brown H4Nb6O17/g-C3N4 composite for visible-light driven H2O2 production. (10th February 2022) - Zhang, Luona; Zhao, Shiqi; Cheng, Xiaorong; Liu, Zijie; Liu, Ruochen; Dawson, Graham
Abstract : Novel, brown H4 Nb6 O17, was synthesised and a composite heterojunction with g-C3 N4 was formed, showing enhanced photocatalytic activity for H2 O2 production. Abstract : A novel form of brown H4 Nb6 O17 was synthesised by annealing niobate nanoscrolls at 300 °C. A composite heterojunction between this brown niobate and g-C3 N4 was formed, and shown to have enhanced photocatalytic activity for the ORR and H2 O2 production of 1.8 μmol after 3 hours. The formation of a heterojunction between the two components was shown to alter the chemical environment and suppress the PL signal, and a band diagram of the system is proposed based on our results.